Pengaruh Promo Diskon dan Experiential Marketing terhadap Penjualan di PT Rekadia Solusi Teknologi - Muhammad Ardissyah Bramasta; Elmira Siska (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Rapid technological innovation affects various aspects of life, including how a company works. One of them is the shift from using paper as a means of writing and files as a means of storage to a computer application commonly known as Microsoft 365 which is cheaper and more efficient. In the world of accounting, there is a trend of increasing performance and time efficiency which is the center of a problem that is quite inflamed by various parties of companies and consumers. This study aims to analyze the influence of discount promo strategies and experiential marketing on sales at PT Rekadia Solusi Teknologi. The approach used is a quantitative method with a population and sample of 34 respondents selected using the saturated sample method. Data were collected through questionnaires, interviews, observations, literature studies, and documentation during the period April - May 2025. Data analysis was carried out using SPSS with data quality tests, classical assumptions, multiple linear regression, t-test, f-test, and coefficient of determination. The results of the study showed that discount promos partially had a positive and significant effect on sales. Experiential marketing also has a positive and significant effect on sales at PT Rekadia Solusi Teknologi. Simultaneously, discount promos and experiential marketing have a positive and significant effect on sales.